2009
DOI: 10.1007/s00109-009-0479-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of endotoxin receptor CD14 polymorphisms on transcriptional activity

Abstract: The polymorphism rs2569190 within the CD14 endotoxin (lipopolysaccharide, LPS) receptor gene is associated with various disease conditions that are assumed to rely on endotoxin sensitivity. In vitro experiments suggest that the T allele sensitizes the host for exogenous or endogenous LPS via an enhanced CD14 expression. To prove the impact of this single nucleotide polymorphism in its natural genomic context in vivo, two parameters of gene transcription were analyzed in peripheral blood mononuclear cells (PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 24 publications
6
25
0
1
Order By: Relevance
“…This, however, could not be verified in vivo because no correlation was found between CD14 mRNA expression in biliary tissue and the CD14 ‐260C>T genotype. These findings are in agreement with earlier reports demonstrating that CD14 levels in freshly isolated peripheral blood mononuclear cells do not correlate with donor rs2569190 polymorphism genotype or haplogenotype . Although local CD14 expression was unaffected, we identified two alternative downstream mechanisms through which TT allele carriers are protected against Gram‐negative colonization of the biliary tree.…”
Section: Discussionsupporting
confidence: 93%
“…This, however, could not be verified in vivo because no correlation was found between CD14 mRNA expression in biliary tissue and the CD14 ‐260C>T genotype. These findings are in agreement with earlier reports demonstrating that CD14 levels in freshly isolated peripheral blood mononuclear cells do not correlate with donor rs2569190 polymorphism genotype or haplogenotype . Although local CD14 expression was unaffected, we identified two alternative downstream mechanisms through which TT allele carriers are protected against Gram‐negative colonization of the biliary tree.…”
Section: Discussionsupporting
confidence: 93%
“…These apparent contradictions need to be considered in the context of differences in population demographics, age and disease context: Munthe-Kaas et al 39 showed that rs2569190 and rs2569191 were associated with serum sCD14 protein levels in Norwegian children up to 2 yrs of age, but not in those older than 2 yrs of age. Others have shown that increased CD14 promoter activity in vitro with rs2569190 and rs2569191 did not translate into increased mRNA levels in population of healthy Caucasian blood donors, 41 and that rs2569190 association with increased sCD14 levels in blood was observed before, but not after, LPS exposure in healthy volunteers in Belgium. 38 …”
Section: Discussionmentioning
confidence: 92%
“…SNP rs2569190, which is located 260 bp 5’ of the human CD14 translation initiation (ATG) codon, had MAFs of 48%, 50%, 49% and 32% in the CEU (n=174 individuals), CHB (n=86), JPT (n=89) and YRI (n=176) populations, respectively, in the International HapMap Project data. This SNP has been widely investigated; alleles have been associated with alterations in transcription (LeVan et al, 2001; Mertens et al, 2009) and in serum sCD14 levels (Kabesch et al, 2004; LeVan et al, 2006; Levan et al, 2008). Thus, a survey of over >500 individuals revealed that there is only one significant SNP in the human population in the 5’ UTR region of CD14.…”
Section: Resultsmentioning
confidence: 99%